Mechanical behavior of synthetic fiber ropes for mooring floating offshore wind turbines. - Ji Zeng; He Zhang; Bowen Jin; Hailei Dong; Chiate Chou; Hangyu Li (PLoS ONE)
The continuous development of floating wind turbine technology is pushing platforms further offshore into deeper seas. Consequently, the water depth required for mooring is increasing, demanding higher standards for the mooring system. This study explores the mechanical properties, including wear resistance and quasi-static stiffness, of nylon, polyester, and high-strength polyethylene mooring ropes through experimental design, aiming to address the challenges faced by floating offshore wind turbines (FOWT) in mooring line safety. In conducting yarn-on-yarn abrasion tests, materials, twist, marine lubricants, and dry and wet environments were chosen as research variables to analyse and compare the wear and tear frequency of sample ropes. The study found that the degree of wear on ropes composed of different materials is affected differently by twist and dry and wet environments, and the application of marine lubricants can significantly extend the friction fracture cycle of yarns. To study the tensile properties and static stiffness characteristics of polyester and nylon ropes, the cables were divided into three stages: preloading, initial installation, and ageing. The strain and reversible elongation of the cables at each stage were analysed, and an empirical formula for quasi-static stiffness considering the creep coefficient of the ropes was established. The study found that the ropes had reversible elongation after being left stationary, the more thorough the running-in, the smaller the inherent deformation, and the more stable the structure. The static stiffness of the cables increased with the loading time and force; however, it eventually approached a constant value, and the stiffness of polyester cables was found to be greater than that of nylon ropes. These results provide a solid theoretical foundation and practical guidance for the material selection of FOWT cables, which contributes to advancing the application and development of FOWT in renewable energy.